Timed Floor to Stand-Natural: Reference Data for School Age Children. Issue 1 (2016) - Weingarten, Goldie; Lieberstein, Michael; Itzkowitz, Adina; Vialu, Carlo; Doyle, Maura; Kaplan, Sandra L.
Abstract : Purpose: To collect reference data for the Timed Floor to Stand-Natural (TFTS-N) on a large, diverse sample of school children who are typically developing, taking into account age, sex, and body mass index (BMI). Methods: Five physical therapists administered the TFTS-N on a sample of convenience of 1476 school children who were typically developing, aged 5 to 14 years (male = 637, female = 839), using previously tested, standardized reliable procedures. Results: The average time ranged from 7.91 ± 1.65 seconds to 8.98 ± 1.62 seconds; 8 year-old students were the quickest and the 13-year-old students were the slowest. The mean difference between males and females was clinically negligible at 0.38 seconds. Post hoc analyses revealed no significant differences among BMI categories. Conclusions: Reference data for the TFTS-N test are now available. Neither sex nor BMI affects the timing of the task in this age range. Abstract : Reference data for the TFTS-N test are available as a result of this study. The authors report that neither gender nor BMI affect the timing of the task in this age range.